FACTORS FOR INCREASING THE EFFICIENCY OF THE LABOR ACTIVITY OF FUTURE VOCAL TEACHERS (Scientific journal of the Fergana State University, 2024)
In Uzbekistan, the attitude towards future academic vocal teachers is of particular importance, and their role in the development of society is highly valued. Academic vocal teachers are people who not only popularize musical knowledge, but also make a great contribution to the overall development, spiritual and cultural enrichment of society. Their activities contribute to the formation of the spiritual environment of society and its sustainable development. This article discusses professional factors that are considered important for improving the activities of future vocal teachers.